2011
DOI: 10.1177/104063871102300107
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Individual Rapid Test Based on Enzymatic Immunofiltration Assay for Detection of Anti–Brucella Abortus Antibody in Bovine Sera

Abstract: To detect bovine antibody directed to smooth lipopolysaccharide (LPS), cell lysate (LYS), O-polysaccharide (OPS), and LPS-deprived chromatographic fractions (ChF) of Brucella abortus, 2 bi-antigenic diagnostic models based on the enzymatic rapid immunofiltration assay (ERIFA), ERIFA(LPS/LYS) and ERIFA(OPS/ChF), were developed. Their diagnostic performance was compared with complement fixation test (CFT), Rose Bengal test (RBT), indirect in-house and commercial enzyme-linked immunosorbent assays (iELISA and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The present study showed the greater affinity of protein G for bovine immunoglobulins compared with protein A, observed in the results of sensitivity and specificity obtained by the LFIA-PG system. Sensitivity and specificity are essential parameters that allow making inferences from the results of an assay (Genç et al, 2011;Ochoa, 2013). Both parameters define the effectiveness of a system since they ensure that the proportion of the infected animals will give positive results to the test; however, the animals still infected give a negative result.…”
Section: Resultsmentioning
confidence: 99%
“…The present study showed the greater affinity of protein G for bovine immunoglobulins compared with protein A, observed in the results of sensitivity and specificity obtained by the LFIA-PG system. Sensitivity and specificity are essential parameters that allow making inferences from the results of an assay (Genç et al, 2011;Ochoa, 2013). Both parameters define the effectiveness of a system since they ensure that the proportion of the infected animals will give positive results to the test; however, the animals still infected give a negative result.…”
Section: Resultsmentioning
confidence: 99%
“…In the LF assay, some specific common antigens, which are surface exposed and important for virulence, are used in the preparation of antibodies that can recognize as many species as possible, such as F1 antigen [22] and plasminogen activator protein [16] of Y. pestis , anthrose tetrasaccharide of B. anthacis [19], outer membrane proteins and O-polysaccharide of Brucella [20], [21], [38]. However, most surface antigens are difficult to isolate and purify because they are amphipathic molecules.…”
Section: Discussionmentioning
confidence: 99%
“…However, traditional LF assays that use colloidal gold as label have the following limitations under potential bioterrorism scenarios with mixed bacteria and complex samples: (i) absence of reactions with different strains of the same pathogen species, (ii) low sensitivities caused by macroscopic observations, (iii) results cannot be analyzed because of serious interferences by colored samples such as whole blood [16], and (iv) inapplicability in extreme conditions (e.g., acid, basic, saline, viscose, and protein-rich solutions) because of the interference in conjugation between antibodies and gold particles that depend on physical adsorption. To simultaneously detect different strains of the same pathogen species, specific antigens are used to prepare antibodies, and two or more antibodies are mixed in LF assays to efficiently recognize species of B. anthracis [19], Brucella [20], [21], and Y. pestis [16], [22] under field conditions. However, only a few works have focused on the rapid detection of pathogens from complex samples using LF assay to meet the requirements of POCT diagnostic and system assessments using extreme reagents and on-site samples.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal cutoff value of the iELISA was determined by ROC analysis as 0.600 (OD 405 ) and 0.500 (OD 405 ) for bovine and ovine sera, respectively. The NERIFA is a version of the ERIFA described previously by Genç et al (2011). Briefly, the NERIFA is essentially based on binding of the conjugate, protein G/colloidal gold particles (G/CG conjugate; Arista Biologicals, USA) to the specific antibodies reacting with Brucella LPS dotted onto a large porous nitro-cellulose filter membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Currently used laboratory-based testing such as complement fixation test (CFT), SAT, enzyme-linked immunosorbent assays (ELISAs), FPA, and recently developed TR-FRET assay (McGiven et al 2009) is inapplicable in field conditions for brucellosis surveillance. In this regard, the lipopolysaccharide (LPS)-based lateral flow (LFA; Abdoel et al 2008) and enzymatic rapid immunofiltration assays (ERIFA; Genç et al 2011) have been recently developed and proposed as field tests for brucellosis diagnosis. Although their usefulness as field tests has been demonstrated, these methods require the use of the species-specific antibodies conjugated with colloidal gold or enzymes as detection reagents.…”
Section: Introductionmentioning
confidence: 99%